The Impact of Stronger Shareholder Control on Bondholders - Amiri-Moghadam, Sadra; Javadi, Siamak; Rastad, Mahdi (Journal of Financial and Quantitative Analysis, 2021)
Abstract We study the impact of stronger shareholder control on bondholders. We find that the passage of shareholder-sponsored governance proposals causes a decline in credit default swap spreads, indicating a net positive effect on bondholders. Evidence suggests that the direct benefit of stronger shareholder control, through the “management disciplining” channel, is larger than the combined adverse effects of directly escalating shareholder-bondholder conflict and indirectly exacerbating exposure to shareholder opportunism. Results are stronger for firms with existing high levels of shareholder-bondholder conflict and for proposals that mitigate managerial entrenchment without exacerbating risk-shifting. Finally, stronger shareholder control improves credit ratings and operating performance in the long-term.